Spillover Effects of Spatial Growth Poles - a Reconciliation of Conflicting Policy Targets? - Alexander Kubis; Mirko Titze; Joachim Ragnitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
Regional economic policy faces the challenge of two competing policy goals - reducing regional economic disparities vs. promoting economic growth. The allocation of public funds has to weigh these goals particularly under the restriction of scarce financial resources. If, however, some region turns out to be a regional growth pole with positive spillovers to its disadvantaged periphery, regional policies could be designed to reconcile the conflicting targets. In this case, peripheral regions could indirectly participate in the economic development of their growing cores. We start our investigation by defining and identifying such growth poles among German regions on the NUTS 3 administrative level based on spatial and sectoral effects. Using cluster analysis, we determine significant characteristics for the general identification of growth poles. Patterns in the sectoral change are identified by means of the change in the employment. Finally, we analyze whether and to what extent these growth poles exert spatial spillover effects on neighbouring regions and thus mitigate contradictory interests in regional public policy. For this purpose, we apply a Spatial-Cross-Regressive-Model (SCR-Model) including the change in the secondary sector which allows to consider functional economic relations on the administrative level chosen (NUTS 3). – – Die Regionalpolitik ist heute im Spannungsfeld zwischen zwei politischen Zielen gefangen, erstens dem Abbau regionaler Disparitäten und zweitens der Initiierung von Wachstumsimpulsen. Die Fördermittelpolitik muss diesen beiden Zielen vor dem Hintergrund enger werdender haushaltspolitischer Spielräume gerecht werden. Wenn stark wachsende Regionen in benachbarte Regionen abstrahlen, dann ist eine Fokussierung der öffentlichen Hilfen auf Wachstumspole sinnvoll. Periphere Regionen partizipieren in diesem Fall indirekt von dem stärkeren Wachstum in den wirtschaftlichen Zentren. Wir identifizieren zunächst auf NUTS 3 Ebene Wachstumsregionen in der Bundesrepublik Deutschland. Mit Hilfe der Clusteranalyse weisen wir nach, dass sich in Wachstumsregionen besondere Muster des Strukturwandels erkennen lassen. Der Strukturwandel wird mit Hilfe von Veränderungen in der Beschäftigungsstruktur analysiert. Zum Schluss wird unter Anwendung eines Spatial-Cross-Regressive-Modells (SCR-Modell) gezeigt, welche Abstrahlwirkungen von den Regionen ausgehen.
urn:nbn:de:gbv:3:2-4073
Keywords: R12; C21; O18; 330; size and spatial distributions of regional economic activity; cross-sectional models; spatial models; treatment effect models; regional; urban; and rural analyses; Entwicklungspol; Spillover-Effekt; Regionale Entwicklung; Regionaler Strukturwandel; Regionalpolitik; Schätzung; Deutschland